Evaluation of life quality of patients submitted to orthognathic surgery - Ana Catarina Alves e Silva; Roberta Almeida Silveira Carvalho; Thiago de Santana Santos; Nelson Studart Rocha; Ana Cláudia Amorim Gomes; Emanuel Dias de Oliveira e Silva (Dental Press Editora, 2013)
OBJECTIVE: To compare changes related to self-esteem and appearance satisfaction between pre and postsurgical phases in patients undergoing orthognathic surgery and to assess the quality of life and psychosocial changes of these patients six months after surgery. METHODS: A longitudinal observational qualitative study was performed. The sample comprised 15 patients with dentofacial deformities who underwent orthognathic surgery. One questionnaire and two forms were answered during pre and postoperative phases. RESULTS: The results showed that 13.3% of patients demonstrated self-esteem improvement, especially in relation to appearance satisfaction. Improvements were also noted in social, occupational and family relationships. With regard to the assessment of quality of life, according to the World Health Organization questionnaire, the lowest improvement averages corresponded to environmental control. CONCLUSION: Orthognathic surgery brings along many emotional changes that should be considered before and after surgery, since the patients' psychological state may be favorable and/or unfavorable during recovery, influencing their quality of life, self-esteem and appearance satisfaction.